IGF-1 Interacted With Obesity in Prognosis Prediction in HER2-Positive Breast Cancer Patients - Tong, Yiwei; Wu, Jiayi; Huang, Ou; He, Jianrong; Zhu, Li; Chen, Weiguo; Li, Yafen; Chen, Xiaosong; Shen, Kunwei (Frontiers in Oncology, 2020)
Purpose: Dysmetabolism and high circulating insulin-like growth factor 1 (IGF-1) would increase breast cancer risk, but its association with survival in HER2+ breast cancer patients has not been well studied. Herein, we aim to evaluate the prognostic value of IGF-1 and metabolic abnormalities in HER2+ population. Patients and methods: HER2+ breast cancer patients treated in Ruijin Hospital between November 2012 and June 2017 were retrospectively analyzed. Median value of circulating IGF-1 was adopted to classify low or high IGF-1 group. Metabolic syndrome (MetS) was defined using AHA/NHLBI criteria. Overweight was defined by body mass index (BMI) ≥ 24.0 kg/m2 in Chinese population. Results: Overall, 679 patients were included and 209 had synchronous MetS. High IGF-1 level was more common in pre/peri-menopausal women (P<0.001) and high IGFBP-3 patients (P<0.001). After a median follow-up of 36 months, 52 patients had disease recurrences. IGF-1 level was not associated with recurrence-free survival (RFS, P=0.620) in the whole population. However, exploratory subgroup analysis found that BMI and IGF-1 interacted in predicting RFS (P=0.009). For non-overweight patients, high IGF-1 showed a superior 4-year RFS (91.1% vs 85.0%; HR 0.53, 95% CI 0.27-1.00, P = 0.049) compared with patients with low IGF-1 level. In contrast, for overweight patients, high IGF-1 was associated with an impaired 4-year RFS (88.3% vs 95.7%, HR 3.20, 95% CI 1.00-10.21, P = 0.038). Furthermore, high IGF-1 level was independently associated with better OS in the whole (HR 0.26, 95% CI 0.08-0.82, P=0.044) as well as non-overweight population (HR 0.15, 95% CI 0.03-0.68, P=0.005). Conclusions: IGF-1 level was not associated with RFS in HER2+ breast cancer patients. However, IGF-1 and BMI had significant interaction in disease outcome prediction in HER2+ patients. High IGF-1 was protective in non-overweight patients, but risk factor for those overweight, which deserves further evaluation.